2011
DOI: 10.1007/s10695-011-9558-0
|View full text |Cite
|
Sign up to set email alerts
|

Brain steroid contents in the catfish Heteropneustes fossilis: sex and gonad stage-specific changes

Abstract: Neurosteroids are those which are synthesized in the central nervous system independently of supply by peripheral endocrine glands. In the present study, brain contents of the steroid hormones, estradiol-17β (E(2)), testosterone (T), corticosteroids, and progestins were investigated in both male and female catfish Heteropneustes fossilis in prespawning (vitellogenic) and spawning (post-vitellogenic) phases using ELISA or HPLC. The data show that the measured steroid hormones showed both stage-specific and sex-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 68 publications
1
8
0
Order By: Relevance
“…Whereas ovarian aromatases are involved in E 2 synthesis in the ovary for vitellogenesis and feedback actions on the brainpituitary axis for the regulation of gonadotropin secretion and sexual behavior, the brain aromatase is implicated in local production of estrogens for both reproductive and non-reproductive functions like neuroprotection and neurogenesis. In the catfish, high levels of E 2 were reported, indicating a local production in the brain (Chaube and Mishra, 2012).…”
Section: Seasonal Variationsmentioning
confidence: 99%
“…Whereas ovarian aromatases are involved in E 2 synthesis in the ovary for vitellogenesis and feedback actions on the brainpituitary axis for the regulation of gonadotropin secretion and sexual behavior, the brain aromatase is implicated in local production of estrogens for both reproductive and non-reproductive functions like neuroprotection and neurogenesis. In the catfish, high levels of E 2 were reported, indicating a local production in the brain (Chaube and Mishra, 2012).…”
Section: Seasonal Variationsmentioning
confidence: 99%
“…Seasonally breeding teleosts like catfish serve as an excellent model for understanding functional significance of neurosteroids. However, from our previous studies on catfish H. fossilis, it has been reported that catfish brain is the site of steroid biosynthesis as we have reported that key steroid biosynthesizing enzyme 3β-HSD and aromatase is localized in the different regions of the catfish H. fossilis brain (Chaube and Mishra, 2012;Chaube et al, 2015;Mishra and Chaube, 2016;Mishra and Chaube, 2017) and this may be involved in the regulation of reproductive activity through its differential distribution.…”
Section: Introductionmentioning
confidence: 87%
“…Steroids are mainly secreted by the gonads and cortex region of adrenal gland, regulating diverse processes of the tissues, including gonads, brain, liver and skeletal muscles (Chaube and Mishra, 2012). They cross blood brain barrier due to their lipophilic nature.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations